Chitosan/PVA Nanofibrous Membranes as Air Filter Material - Ramadhan, Muhammad; Yuda, F.A. Kusuma; Yusmaniar, Yusmaniar; Iriani, Yofentina; Sosiati, Harini; Suhandra, Izon (Materials science forum, 2022)
Nanofiber membranes made of polymer materials are being extensively investigated and developed as air filter materials. This research aims to make and characterize the nanofiber membranes as filter materials capable of filtering gaseous pollutants from cigarette smoke. The electrospinning method manufactured the chitosan (CS)/PVA blend nanofiber membranes with CS/PVA ratios of (0/100, 20/80, 30/70, and 40/60 w/w) using low molecular weight (LMw) PVA and the ratios of (0/100, 10/90, 20/80, and 30/70 w/w) with high Mw (HMw) PVA. The CS concentration increased the CS-PVA solution‘s electrical conductivity and decreased the membrane‘s average fiber diameter and tensile properties. The filtration test on neat PVA and CS/LMw PVA (20/80) membranes set on the metallic substrate with a 0.08 mm hole size was conducted by varying membrane thickness (20, 35, and 45 µm). The filtration efficiency increased with the membrane thickness because membrane pores tend to be smaller, indicating that reducing the fiber diameter by adding CS increases pore size. The filtration test on CS/HMw PVA (20/80) membranes with 45 µm thickness on different substrate¢s hole sizes of (0.08, 1.19, and 1.41 mm) showed that the larger the hole size, the lower the filtration efficiency. By similar CS/PVA ratio, membrane thickness, and substrate size hole, the CS/HMw PVA's filtration efficiency (87.15%) is higher than CS/LMw PVA (85.79%). However, the CS/LMw PVA membrane showed higher tensile strength, low stiffness, and more economical air filtration material than CS/HMw PVA.